Estudo de primeiros princípios da interacão de monóxido de carbono com nanotubos de carbono semicondutores - Silva, Leandro Barros da (2004)
In this work we study the interaction of carbon monoxide with semiconducting (8,0)carbon nanotube through a first principles theoretical approach. Using density functional theory based methods, we show that radial deformation produces alterations in the band structure of the nanotubes, with a monotonically decreasing energy gap as the tube is deformed. Such deformation modifes the electronic population of the orbitals, leading to an increasing in charge density in the most curved regions, augmenting the chemical reactivity in such regions. We show that the process is reversible and follows the classical laws of elasticity, where total energy is a quadratic function of the parameter є. We study the energetic, structural and electronic properties of carbon nanotubes substitucionally doped by silicon. We show that the sistem is stable, with formation energy 2,96 eV, and semiconducting with energy gap of 0,57 eV, presenting an unnocupied level 0,24 eV bellow the conducting band bottom. The charge density of that orbital points to a highly reactible site over the dopant. The interaction of carbon nanotubes with carbon monoxide was simulated through the analisis of several initial configurations, where molecule occupies different sites over the surface of the tube. In regular non-deformed nanotubes, the analisis of the band structure, orbital population and state and charge densities indicates no interaction between molecule and tube, whereas in deformed and/or doped nanotube a covalent bond is formed for at least one surface site. In є = 0; 3 deformed nanotubes and silicon doped regular nanotubes the moleculetube binding energy is 0,51 eV. The adsorption modifes the band structure in such a way the originally metallic system turns a semicondutor with energy gap of 0,36 eV. In doped nanotubes, the interaction induces a redution in the energy gap to 0,36 eV. Finally, we analise the effects over carbon monoxide adsorption of simultaneous radial deformation and silicon doping. The binding energy is 0,53 eV, the largest among the studied sistems. The adsorption leads to an energy gap of 0,08 eV. The process has total formation energy of 5,83 eV, by far the less energetically favorable. As a complementary result, we show that deformed nanotubes with a single vacancy present new chemical and physical properties, and we analise the dependence of such characteristics with the order where the process ocurres, both deformation followed by vacancy creation and vacancy creation followed by radial deformation.